2021
DOI: 10.3390/su13094768
|View full text |Cite
|
Sign up to set email alerts
|

VAT Efficiency—A Discussion on the VAT System in the European Union

Abstract: The effectiveness of the tax system can be analysed in various ways. According to the authors one of manifestations of such effectiveness is resistance to tax evasion. This phenomenon is influenced by multiple factors, with few being the level of VAT rates and the number of rates in force in the country concerned. The aim of the considerations is therefore to analyse how the standard VAT rate as well as the number of rates affect the effectiveness of this tax. The research was based on a literature query in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…Our findings are not comparable with the study provided recently by Kowal and Przekota (2021), which, although it classified the EU countries similarly into 6 categories, it did so according to the VAT gap reduction trend in the past period. The research study provided by Kasnauskienė and Krimisieraitė (2015) was also realised only in the case of an individual country Lithuania.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are not comparable with the study provided recently by Kowal and Przekota (2021), which, although it classified the EU countries similarly into 6 categories, it did so according to the VAT gap reduction trend in the past period. The research study provided by Kasnauskienė and Krimisieraitė (2015) was also realised only in the case of an individual country Lithuania.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that tax gaps in the EU member states have been growing every year. Other recent research of tax evasion and the tax gap in the EU countries for the period between 2011 and 2019 were realized recently by Kowal and Przekota (2021). The efficiency of VAT collection in the EU countries was modelled using a square function, determining the significance of the parameters of this function.…”
Section: Previous Research Studies Conducted In the Eu Countriesmentioning
confidence: 99%
“…Noting the negative impact of VAT fraud, certain researchers conclude that this illegal activity creates some of the most dangerous consequences for an economy [14,15] and proclaim that such activity can be implicated in the direct or indirect financing of terrorism [16]. The most important instrument for combatting VAT fraud is the development of international cooperation [17] and use of modern technologies [18].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies indicate that transformations in the field of taxation, including international taxation, ensure a sustainable development trend [23,24]. Kowal [18] highlighted the demonstrated efficiencies of a tax system through the degree of resistance that system poses to tax evasion.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a team of authors analyzed the factors defining the parameters of VAT gap in an economy and concluded that three key categories of actors-final consumers, sellers, and the tax administration-must ensure the good-faith fulfillment of their duties (Poniatowski et al 2020). Noting the negative impact of VAT fraud, certain researchers concluded that this illegal activity creates some of the most dangerous consequences for an economy (Fjeldstad et al 2020;Pouwels 2021), and also concluded that such activity could be implicated in direct or indirect financing of terrorism (Frunza 2018); the most important instrument for combatting VAT fraud is the development of international cooperation (Ding et al 2021) and use of modern technologies (Kowal and Przekota 2021).…”
mentioning
confidence: 99%